10 Amazing Facts about Mathematics / Siti Zaharah Mohd Ruslan - Mohd Ruslan, Siti Zaharah (FSKM Universiti Teknologi MARA (UiTM) Cawangan Negeri Sembilan, 2020)
What do you think? Formula, equation and calculation sounds boring for those who hate mathematics as a subject. However, the fact remains that it is an essential subject for students. Even though numbers can be scary sometimes, but if they learned them and with fun, they can be amazing and cool. Let's see few interesting and amazing facts about mathematics.